Performance-based comparison of Xue and Yamada-Ota models of ternary hybrid nanofluid flow over a slendering stretching sheet with activation energy and melting phenomena - Abbas, Munawar; Khan, Nargis; Alshomrani, Ali Saleh; Hashmi, M. S.; İnç, Mustafa (Elsevier, 2023)
The practical applications of current model include materials science, heat exchangers, renewable energy, nanotechnology, manufacturing, medical treatments, and environmental engineering. Insights gained from this study could enhance material design, improve heat transfer efficiency in various systems, optimize energy conversion processes, and contribute to advancements in nanotechnology, medical therapies, and engineering design. In this investigation, melting heat transmission and non-uniform heat generation features of ternary hybrid nanofluid flow over a slender stretched sheet are examined. This proposed model goal is to compare the effectiveness of the well-known ternary hybrid nanofluid models Xue and Yamada-Ota. Utilized is a ternary hybrid nanofluid made up of titanium oxide (TiO2), aluminum oxide (Al2O3), cobalt iron oxide (CoFe2O4), and Ethylene glycol (C2H6O2) as the base fluid. The course leading equations are transformed using appropriate similarity variables, and the following equations are then mathematically solved using the shooting approach (bvp4c). The impacts of some physical parameters on the typical profiles (concentration, velocity and thermal) are explained using the Xue and Yamada-Ota models. Additionally, the same parameters are used to explore the mass and heat transfer rates, and the results are shown in tabular format. For higher values of wall thickness parameter, the velocity and thermal profiles enhance. It also reduces the rates of mass and heat transmission. The Yamada-Ota model outperforms the Xue ternary hybrid nanofluid model in terms of heat and mass transfer efficiency.
Keywords: Ternary hybrid nanofluid; Non-uniform heat source; Melting phenomena; Xue and Yamada-Ota; Activation energy